2018
DOI: 10.1002/ece3.3895
|View full text |Cite
|
Sign up to set email alerts
|

The fitness effects of delayed switching to sex in a facultatively asexual insect

Abstract: Facultative reproductive strategies that incorporate both sexual and parthenogenetic reproduction should be optimal, yet are rarely observed in animals. Resolving this paradox requires an understanding of the economics of facultative asexuality. Recent work suggests that switching from parthenogenesis to sex can be costly and that females can resist mating to avoid switching. However, it remains unclear whether these costs and resistance behaviors are dependent on female age. We addressed these questions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Asexual reproduction is thought to maintain a population of locally adapted clones (Ayre & Miller, 2004) and less costly than sexual reproduction (Rispe, Pierre, Simon, & Gouyon, 1998). For this reason, asexual reproduction can be advantageous for animals in good conditions and early in their life, since they can rapidly colonize resources for their own genotype, while later they can use more costly sexual reproduction to increase genotypic diversity (Burke & Bonduriansky, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asexual reproduction is thought to maintain a population of locally adapted clones (Ayre & Miller, 2004) and less costly than sexual reproduction (Rispe, Pierre, Simon, & Gouyon, 1998). For this reason, asexual reproduction can be advantageous for animals in good conditions and early in their life, since they can rapidly colonize resources for their own genotype, while later they can use more costly sexual reproduction to increase genotypic diversity (Burke & Bonduriansky, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous findings in other partially clonal species. For instance, female stick insects that mated in early life (prior to the start of parthenogenetic reproduction) produce fewer eggs, possibly because they were not fully mature at pairing (Burke & Bonduriansky, 2018). Age‐dependent sexual maturity is also known in some coral species (Kai & Sakai, 2008), while in Pelmatohydra robusta (likely synonymous to H. oligactis ; Schwentner & Bosch, 2015) a decreased sexual maturation time and increased fecundity with polyp age were reported previously by Noda (1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some species, delayed mating can increase adult longevity [25,43,81]. This is widely considered to be a result of the reduced energy expenditure associated with reproduction [82,83]. However, Omkar et al [34] and Bakker et al [84] showed that mating delays may be responsible for reducing adult longevity in Zygogramma bicolorata, Y. padellus (L.) (Lepidoptera: Yponomeutidae), and Anastrepha ludens Loew (Diptera: Tephritidae), possibly due to males deliberately harming females in order to stimulate a higher oviposition rate; the increased activity of females, including efforts spent in locating a mate prior to mating, i.e., crawling, flying, etc., and afterwards seeking a suitable oviposition medium; and, in males, the process of ejaculation consuming a portion of their energy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cases of post‐copulatory parthenogenesis are extremely rare (e.g., see Arbuthnott, Crespi, & Schwander, ; Chang, Ting, Chang, Fang, & Chang, ), which suggests that coerced fertilization of eggs by sperm may further limit parthenogenetic reproduction. Fourth, fitness costs associated with switching from a parthenogenetic to sexual mode of reproduction could be an additional hurdle (Burke & Bonduriansky, ; Burke et al., ). Such constraints on parthenogenetic reproduction could therefore play key roles in preventing facultative mutants from invading obligately sexual populations.…”
Section: Discussionmentioning
confidence: 99%